Comparisons between TOMS, TOVS and DOBSON observations - Satellite and surface views of total column ozone - Chesters, Dennis; Neuendorffer, Arthur (1990)
The reliability of the ozone retrievals by the TIROS-N Operational Vertical Sounder (TOVS) calculated with the newly developed physical algorithm is investigated by comparing the quality of the TOVS total ozone soundings to the corresponding values obtained by the Nimbus-7 TOMS and by the ground-based DOBSON network. The three-way comparison concentrates on observations during the last 4 months of 1987, the period of the great Antarctic 'ozone hole'. It is shown that each instrument has characteristic strengths and weaknesses, and that each of the three systems makes serious errors under some conditions.